Some Issues on Studying Material Culture “Ancient Ustrushana” - Tuychibaev Bahodir Basymovich (Zien Journals, 2022)
The following article discusses with individual problems of the development of material culture of the Ustrushana since the epoch of the Early Iron Age, based on generalizations, analysis and systematization of the conclusions of archaeological research. In particular: the issues of the genesis and continuous development of the settled agricultural culture of the peoples of the Ustrushana, starting from the Early Iron Age and its spread throughout the region, as well as the role and place of socio-economic conditions in the formation of the local highly developed material culture are considered. The development of the urbanization process of the region, the origins of the origin and development of artificial irrigation skills are traced, and a range of issues of material culture such as change and development in architecture, handicraft production and others are also considered. In conclusion, from the analysis of the conducted research, the following conclusions are presented, which allows identifying the main directions in the study of the material culture of Ustrushana. Such as the emergence of early settlements, the area of distribution of local culture, urban planning and urbanization processes, handicraft production and its development, monuments of art, as well as issues of historical topography, political, socio-economic and cultural life of the “ancient ustrushana” territory
Keywords: Ancient Ustrushana; territory; history of archaeological study of the region; Basmandasay